Development and Characterization of Three-Dimensional Lattice Hydroxyapatite Scaffolds Using Aqueous Based Extrusion Fabrication (ABEF) for Biomedical Applications - Muhammad Kusumawan Herliansyah; Y Nugroho (Journal of Material Processing and Characterization, 2020)
A solid freeform fabrication technique, aqueous based extrusion fabrication (ABEF), was investigated for the creation of three-dimensional lattice Hydroxyapatite scaffolds with pre-designed pore properties. An aqueous based Hydroxyapatite paste was extruded through a 0.8 mm nozzle, and deposited layer-by-layer at room temperature according to a computer-aided design (CAD) file. The morphology of green body and sintered body were characterized using digital microscope. The phase purity was analyzed using XRD. Fourier transform infrared spectroscopy (FTIR) was performed in order to understand the phase changes upon heating process and to determine HA stoichiometry. The current investigation confirms the possibility of producing three-dimensional lattice Hydroxyapatite scaffolds without any impurities as indicated by XRD and FTIR techniques. The morphology analysis of the structured macroporous Hydroxyapatite bioceramic shows interconnected macro pores and micro pores. It will give possibility for colonization of osteoblast in the pores, fibrovascular ingrowth and finally the deposition of new bone formation.